An Accelerated Release Study to Evaluate Long-Acting Contraceptive Levonorgestrel-Containing in Situ Forming Depot Systems - Dileep R. Janagam; Lizhu Wang; Suryatheja Ananthula; James R. Johnson; Tao L. Lowe (MDPI AG, 2016)
Biodegradable polymer-based injectable in situ forming depot (ISD) systems that solidify in the body to form a solid or semisolid reservoir are becoming increasingly attractive as an injectable dosage form for sustained (months to years) parenteral drug delivery. Evaluation of long-term drug release from the ISD systems during the formulation development is laborious and costly. An accelerated release method that can effectively correlate the months to years of long-term release in a short time such as days or weeks is economically needed. However, no such accelerated ISD system release method has been reported in the literature to date. The objective of the current study was to develop a short-term accelerated in vitro release method for contraceptive levonorgestrel (LNG)-containing ISD systems to screen formulations for more than 3-month contraception after a single subcutaneous injection. The LNG-containing ISD formulations were prepared by using biodegradable poly(lactide-co-glycolide) and polylactic acid polymer and solvent mixtures containing N-methyl-2-pyrrolidone and benzyl benzoate or triethyl citrate. Drug release studies were performed under real-time (long-term) conditions (PBS, pH 7.4, 37 °C) and four accelerated (short-term) conditions: (A) PBS, pH 7.4, 50 °C; (B) 25% ethanol in PBS, pH 7.4, 50 °C; (C) 25% ethanol in PBS, 2% Tween 20, pH 7.4, 50 °C; and (D) 25% ethanol in PBS, 2% Tween 20, pH 9, 50 °C. The LNG release profile, including the release mechanism under the accelerated condition D within two weeks, correlated (r2 ≥ 0.98) well with that under real-time conditions at four months.